Distance Learning in Higher Education During Covid-19 - Masalimova, Alfiya R.; Khvatova, Maria A.; Chikileva, Lyudmila S.; Zvyagintseva, Elena P.; Stepanova, Valentina V.; Melnik, Mariya V. (Frontiers in Education, 2022)
The mini-review aims to ascertain students' attitudes about distant learning during COVID-19. To accomplish the objective, articles were retrieved from the ERIC database. We utilize the search phrases "Distance learning" AND "University" AND "COVID" We compiled a list of 139 articles. We chose papers with "full text" and "peer reviewed only" sections. Following the exclusion, 58 articles persisted. Then, using content analysis, publications relating to students' perspectives on distance learning were identified. There were 27 articles in the final list. Students' perspectives on distant education are classified into four categories: perception and attitudes, advantages of distance learning, disadvantages of distance learning, and challenges for distance learning. In all studies, due of pandemic constraints, online data gathering methods were selected. Surveys and questionnaires were utilized as data collection tools. When students are asked to compare face-to-face and online learning techniques, they assert that online learning has the potential to compensate for any limitations caused by pandemic conditions. Students' perspectives and degrees of satisfaction range widely, from good to negative. Distance learning is advantageous since it allows for learning at any time and from any location. Distance education benefits both accomplishment and learning. Staying at home is safer and less stressful for students during pandemics. Distance education contributes to a variety of physical and psychological health concerns, including fear, anxiety, stress, and attention problems.